2013
DOI: 10.1016/j.jor.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with isolated femoral shaft fractures treated with S.I.G.N interlock nails versus Cannulated Interlock Intramedullary nails

Abstract: There is no significant difference between patients with isolated femoral shaft fractures treated with S.I.G.N. Interlock Intramedullary nail versus Cannulated Interlock Intramedullary nail in terms of Clinical and radiographic union, weight bearing, knee range of motion and complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…(2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Despite their use of heterogeneous outcome measurements, these SIGN nail results have been found to be comparable to those from other studies that evaluated more traditional cannulated interlocking intramedullary nails. (2,12) There are several limitations of the current study. The SIGN database we used has the potential for lack of input standardization and quality control, given that data is entered by surgeons around the world.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…(2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Despite their use of heterogeneous outcome measurements, these SIGN nail results have been found to be comparable to those from other studies that evaluated more traditional cannulated interlocking intramedullary nails. (2,12) There are several limitations of the current study. The SIGN database we used has the potential for lack of input standardization and quality control, given that data is entered by surgeons around the world.…”
Section: Discussionmentioning
confidence: 86%
“…(2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Complications found by prior studies have included delayed union in 4-34% of patients, and infection in 1-11%, implant failure in 3-4%. (2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Despite their use of heterogeneous outcome measurements, these SIGN nail results have been found to be comparable to those from other studies that evaluated more traditional cannulated interlocking intramedullary nails. (2,12) There are several limitations of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Multiple studies have subsequently shown that the SIGN nail is an effective treatment choice in these circumstances, with union rates above 90% in multiple series. [ 9 , 11 , 12 , 18 – 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Multiple studies have subsequently shown that the SIGN nail is an effective treatment choice in these circumstances. [ 12 , 14 , 15 , 20 – 22 ] Carsen et al [ 23 ] recently analyzed the postoperative radiographs of 500 cases in which the standard SIGN nail was used to treat fractures of the femoral shaft. The authors found that 10% of cases demonstrated fracture malalignment greater than 5°.…”
Section: Discussionmentioning
confidence: 99%